Review on Real Time Approach for Smart Agriculture Based on IoT and Raspberry Pi 3 - Shinde, Rasika; Shinde, Sagar (International Journal of Computer Sciences and Engineering, 2019)
Smart agriculture is taking over traditional farming due to the evolution of the IoT (Internet of Things). Automatic irrigation systems as well as monitoring of environmental parameters are the key factor of proposed system. In this project, we have proposed Real time approach for smart agriculture based on IoT and Raspberry pi 3. For monitoring environmental parameters proposed system have used different sensors like soil moisture sensor, thermistor, DHT11 sensor, Gas sensor. These sensors are connected to ESP8266MOD through MCP3204.Proposed systems have used four nodes at four different farm fields which communicates with Raspberry pi 3 over Wi-Fi. Data from all sensors of all nodes is shown on webpage. Also if any sensor value exceeds threshold level, email alert is sent. If the soil moisture sensor of any node exceeds threshold value motor will be automatically OFF. Using past environmental data of all fields farmers can take better decision for future farming like which crop has to be planted at which period and at which field.